Flavor hierarchies from emergent fundamental partial compositeness - Goertz, Florian; Pastor-Gutiérrez, Álvaro; Pawlowski, Jan M. (Physical review, 2023)
Composite Higgs extensions of the Standard Model provide an explanation for the large hierarchies between the Yukawa couplings. We study their realization in the context of fundamental partial compositeness where the Standard Model fermions mix linearly with bound states of the new sector, consisting of a fermion and a scalar. The properties of this composite are unraveled with the functional renormalization group approach using dynamically emergent composites. Specifically, we extract the scaling of correlation functions along a walking regime and provide indicative estimates for the minimal incarnation of the theory.